Composition, conductive film, capacitor, and battery

By using a composition doped with a polyaniline composite and a phenol compound, the problem of difficult balance of the conductive polymer film viscosity and conductivity is solved, and the effect of controlling the viscosity within a wide range and maintaining high conductivity is achieved.

CN119137220APending Publication Date: 2024-12-13IDEMITSU KOSAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040070.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-24
Filing Date
2023-05-17
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, when adjusting the viscosity of the conductive polymer film, it is usually necessary to change the concentration or add a large amount of binder, resulting in high cost or reduced conductivity, making it difficult to control the viscosity within a wide range and maintain the conductivity.

Method used

Using a composition containing conductive polymers, phenol compounds, tackifiers and solvents, the viscosity and conductivity of the composition are optimized by doping proton donors, combining the synergy between phenol compounds and cellulose-based compounds. Effects, achieving balance of viscosity and conductivity.

Benefits of technology

Without increasing costs, the viscosity of the composition is significantly improved and the conductivity is maintained within the practical range, suitable for coating and printing processes, and the durability and conductivity of the film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A composition containing (a) a conductive polymer, (b) a phenol compound, (c) a tackifier, and (d) a solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition, a conductive film, a capacitor and a battery. Background Art

[0002] Conductive polymers are used as solid electrolytes for capacitors, electromagnetic wave absorbing coatings, antistatic coatings, plating base materials, conductive inks for circuit wiring, etc.

[0003] Polyaniline, which is a kind of conductive polymer, has advantages and characteristics such as being able to be synthesized relatively easily from inexpensive aniline in addition to its electrical properties and being excellently stable against oxygen and the like while exhibiting conductivity.

[0004] According to the method described in Patent Document 1, highly conductive polyaniline can be easily obtained.

[0005] Conductive polymers are usually insoluble and infusible, making them difficult to shape. In recent years, water-dispersible or organic solvent-soluble conductive polymers have been developed, making shaping and processing easier. Conductive polymer films can be formed by coating and printing, and various functionalities can be imparted.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Patent Publication No. 2012 / 102017 Summary of the invention

[0009] An object of the present invention is to provide a composition, a conductive film, a capacitor, and a battery capable of achieving an excellent viscosity increase exceeding the effect of simply adding a thickener.

[0010] There is a viscosity that is more suitable for coating and printing methods. Usually, in order to adjust the viscosity, it is necessary to change the concentration of the conductive polymer or the solvent composition. In this case, if the concentration of the conductive polymer is increased, the viscosity becomes higher, but the cost as a material becomes higher, which is not practical. If the concentration is reduced, the viscosity becomes lower, but it becomes a very thin coating film with low durability and a high resistance film, which is also not practical.

[0011] In addition, a large amount of a binder may be blended to increase the viscosity, but in this case, the conductivity of the resulting coating film is significantly reduced.

[0012] The present inventors have found a composition capable of obtaining a conductive film having a viscosity controlled within a wide range and having conductivity maintained within a practical range, thereby completing the invention.

[0013] According to the present invention, the following compositions and the like are provided.

[0014] 1. A composition comprising:

[0015] (a) Conductive polymer;

[0016] (b) phenolic compounds;

[0017] (c) tackifiers; and

[0018] (d) Solvent.

[0019] 2. The composition according to item 1, wherein the component (a) is a polyaniline composite in which a proton donor is doped in a substituted or unsubstituted polyaniline.

[0020] 3. The composition according to 2, wherein the proton donor is a proton donor represented by the following formula (I).

[0021] M(XARn)m(I)

[0022] (In formula (I), M is a hydrogen atom, an organic free radical or an inorganic free radical.

[0023] X is an acidic group. A is a hydrocarbon group which may have a substituent.

[0024] R is each independently -R 1 、-OR 1 、-COR 1 、-COOR 1 、-CO(COR 1 ), or -CO (COOR 1 ) is a substituent shown in FIG.

[0025] R 1 is a hydrocarbon group having 4 or more carbon atoms which may contain a substituent, a silyl group, an alkylsilyl group, -(R 2 O) x -R 3 The group shown, or -(OSiR 3 2 ) x -OR 3 (R 2 is an alkylene group, R 3 wherein each of them is a hydrocarbon group which may be the same or different, and x is an integer greater than 1).

[0026] n is an integer greater than or equal to 2.

[0027] m is the valence of M. )

[0028] 4. The composition according to any one of 1 to 3, wherein the content of the component (c) is 0.1% by mass or more based on 100% by mass of the entire composition.

[0029] 5. The composition according to any one of 1 to 4, wherein a mass ratio of the content of the component (a) to the content of the component (c) is 1:0.01 to 1:2.

[0030] 6. The composition according to any one of 1 to 5, wherein the component (c) is a polyether compound or a cellulose compound.

[0031] 7. The composition according to any one of 1 to 6, which has a viscosity of 2 to 1000 mPa·s.

[0032] 8. A conductive film formed using the composition according to any one of 1 to 7.

[0033] 9. A capacitor comprising the conductive film according to 8.

[0034] 10. A battery comprising the conductive film according to 8.

[0035] According to the present invention, it is possible to provide a composition, a conductive film, a capacitor, and a battery capable of achieving an excellent viscosity increase exceeding the effect of simply adding a thickener. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a diagram showing the upper surface of a glass substrate used in Example 1, on which an indium tin oxide (ITO) electrode is formed.

[0037] Figure 2 This is a view showing the upper surface of the glass substrate produced in Example 1, in which the conductive film is cut to expose the terminal of the ITO electrode on the surface.

[0038] Figure 3 This is a graph showing the synergistic effect of component (b) and component (c). DETAILED DESCRIPTION

[0039] [Composition]

[0040] A composition according to one embodiment of the present invention comprises

[0041] (a) a conductive polymer (hereinafter also referred to as “component (a)”);

[0042] (b) a phenol compound (hereinafter, also referred to as “component (b)”);

[0043] (c) a tackifier (hereinafter, also referred to as "ingredient (c)"); and

[0044] (d) Solvent (hereinafter, also referred to as “component (d)”).

[0045] This can achieve an excellent viscosity increase that exceeds the effect of simply adding a thickener.

[0046] In addition, as an optional effect, the conductivity of the obtained conductive film (for example, 0.5 S / cm or more) and the viscosity of the composition can be achieved at the same time.

[0047] From the viewpoint of coating properties, the viscosity of the composition of one embodiment of the present invention is, for example, 1 to 500 mPa·s, 2 to 500 mPa·s, 3 to 400 mPa·s, 5 to 300 mPa·s, 1 to 1000 mPa·s, 2 to 1000 mPa·s, 3 to 700 mPa·s, 10 to 500 mPa·s, or 16 to 200 mPa·s.

[0048] The viscosity of the composition was measured using a tuning fork vibration viscometer SV-1H (manufactured by A&D Corporation).

[0049] Hereinafter, each component will be described.

[0050] (Component (a): conductive polymer)

[0051] As the conductive polymer, polyaniline, polythiophene, polypyrrole and their derivatives can be mentioned. These may have a substituent or may not have a substituent. These may be used alone or in combination of two or more.

[0052] As the conductive polymer, polyaniline is preferred.

[0053] The weight average molecular weight of polyaniline is preferably 10,000 or more, more preferably 20,000 or more, further preferably 30,000 or more and 1,000,000 or less, further preferably 40,000 or more and 1,000,000 or less, and particularly preferably 52,000 or more and 1,000,000 or less.

[0054] The weight average molecular weight of polyaniline is measured by the method described in Examples.

[0055] The polyaniline may or may not have a substituent, but is preferably an unsubstituted polyaniline from the viewpoint of versatility and economic efficiency.

[0056] When the substituent has a substituent, for example, a straight-chain or branched hydrocarbon group such as methyl, ethyl, hexyl, octyl, etc.; an alkoxy group such as methoxy, ethoxy, etc.; an aryloxy group such as phenoxy, etc.; a trifluoromethyl group (-CF 3 alkyl) and other halogenated hydrocarbons.

[0057] In addition, from the viewpoint of conductivity, a polyaniline composite obtained by doping a proton donor into a substituted or unsubstituted polyaniline is preferred.

[0058] The doping of the proton donor in polyaniline can be confirmed by ultraviolet, visible, and near-infrared spectroscopy and X-ray photoelectron spectroscopy, and the proton donor can be used without particular limitation in terms of chemical structure as long as it has acidity sufficient to generate carriers in polyaniline.

[0059] By using the polyaniline composite, the solubility in a solvent is improved, which is preferable.

[0060] Examples of the proton donor include Bronsted acids or salts thereof, preferably organic acids or salts thereof (such as sulfonic acids or sulfonates), and more preferably a proton donor represented by the following formula (I) from the viewpoint of solubility.

[0061] M(XAR n ) m (I)

[0062] (In formula (I), M is a hydrogen atom, an organic free radical or an inorganic free radical.

[0063] X is an acidic group. A is a hydrocarbon group which may have a substituent.

[0064] R is each independently -R 1 、-OR 1 、-COR 1 、-COOR 1 、-CO(COR 1 ) or -CO (COOR 1 ) is a substituent shown in FIG.

[0065] R 1 is a hydrocarbon group having 4 or more carbon atoms which may contain a substituent, a silyl group, an alkylsilyl group, -(R 2 O) x -R 3 The group shown, or -(OSiR 3 2 ) x -OR 3 (R 2 is an alkylene group, R 3 wherein each of them is a hydrocarbon group which may be the same or different, and x is an integer greater than 1).

[0066] n is an integer greater than or equal to 2.

[0067] m is the valence of M. )

[0068] In the above formula (I), M is a hydrogen atom, an organic free radical or an inorganic free radical.

[0069] Examples of the organic radical include a pyridinium group, an imidazolium group, an anilinium group, etc. Examples of the inorganic radical include sodium, lithium, potassium, cesium, ammonium, etc.

[0070] X is an acidic group, for example -SO 3 - ,-PO 3 2- ,-PO 4 (OH) - ,-OPO 3 2- ,-OPO 2 (OH) - 、-COO - The groups shown in the figure are preferably -SO 3 - The groups shown.

[0071] A is a hydrocarbon group which may have a substituent.

[0072] Examples of the hydrocarbon group include a linear or branched alkyl group (e.g., ethylene) having 1 to 24 carbon atoms (preferably 1 to 8, more preferably 1 to 4); an alkenyl group; a cycloalkyl group which may have a substituent, such as a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a menthyl group, etc.; a bicycloalkyl group or a polycycloalkyl group which may be condensed, such as a bicyclohexyl group, a norbornyl group, an adamantyl group, etc.; an aromatic ring-containing aryl group which may have a substituent, such as a phenyl group, a tosyl group, a thienyl group, a pyrrolinyl group, a pyridyl group, a furyl group, etc.; a diaryl group or a polyaryl group which may be condensed, such as a naphthyl group, anthracenyl group, a fluorenyl group, a 1,2,3,4-tetrahydronaphthyl group, an indanyl group, a quinolyl group, an indolyl group, etc.; and corresponding (n+1)-valent groups.

[0073] R is each independently -R 1 、-OR 1 、-COR 1 、-COOR 1 、-CO(COR 1 ) or -CO (COOR 1 ) is a substituent shown in FIG.

[0074] R 1 is a hydrocarbon group having 4 or more carbon atoms (e.g., 4 to 8 or 4 to 12) which may have a substituent (e.g., an alkyl group having 1 to 4 carbon atoms (preferably a methyl group, an ethyl group, or a propyl group)), a silyl group, an alkylsilyl group, -(R 2 O) x -R 3 The group shown, or -(OSiR 3 2 ) x -OR 3 (R2 is an alkylene group, R 3 wherein each of them is a hydrocarbon group which may be the same or different, and x is an integer greater than 1).

[0075] As R 1 Examples of the hydrocarbon group include linear or branched butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, pentadecyl, eicosyl and the like.

[0076] n is an integer of 2 or more (eg, 2 to 4 or 2 to 3).

[0077] m is the valence of M.

[0078] The proton donor represented by the formula (I) is preferably a dialkylbenzenesulfonic acid, a dialkylnaphthalenesulfonic acid, a sulfophthalate, or a proton donor represented by the following formula (II) (organic protonic acid or a salt thereof).

[0079] M(XCR 4 (CR 5 2 COOR 6 )COOR 7 ) p (II)

[0080] In the above formula (II), M and X are the same as in formula (I).

[0081] p is the valence of M.

[0082] R 4 and R 5 are each independently a hydrogen atom, a hydrocarbon group or R 8 3 The group represented by Si- (here, R 8 is a hydrocarbon group, 3 R 8 can be the same or different).

[0083] As R 4 and R 5 The hydrocarbon group includes a linear or branched alkyl group having 1 to 24 carbon atoms; an aryl group containing an aromatic ring; an alkylaryl group, and the like.

[0084] R 8 The hydrocarbon group and R 4 and R 5 The hydrocarbon groups are the same.

[0085] R 6 and R 7 Each independently is a hydrocarbon group or -(R 9 O) q -R 10 The group shown [here, R 9is a hydrocarbon group or a silylene group, R 10 is a hydrogen atom, a hydrocarbon group or R 11 3 The group represented by Si- 11 is a hydrocarbon group, 3 R 11 may be the same or different), q is an integer greater than 1].

[0086] As R 6 and R 7 The hydrocarbon group includes a linear or branched alkyl group having 1 to 24 carbon atoms, preferably 4 or more carbon atoms (eg 4 to 10 or 4 to 14); an aryl group including an aromatic ring; an alkylaryl group, and the like.

[0087] As R 6 and R 7 Specific examples of the hydrocarbon group include linear or branched butyl, pentyl, hexyl, octyl (eg, 2-ethylhexyl), decyl, and the like.

[0088] As R 9 The hydrocarbon group is a straight-chain or branched alkylene group having 1 to 24 carbon atoms; an arylene group containing an aromatic ring; an alkylarylene group; an arylalkylene group, and the like.

[0089] In addition, as R 10 and R 11 The hydrocarbon group, with R 4 and R 5 The same is true for the case of q. Preferably, q is an integer of 1 to 10.

[0090] As R 6 and R 7 =R 9 O) q -R 10 Specific examples of the proton donor acid represented by formula (II) in the case of a group represented by include acids represented by the following formulas.

[0091]

Chemical formula 1

[0092]

[0093] (Where X is -SO 3 The groups shown, etc.)

[0094] The proton donor (organic protonic acid or a salt thereof) represented by the above formula (II) is preferably a sulfosuccinic acid derivative represented by the following formula (III).

[0095] M(O 3 SCH(CH 2 COOR 12 )COOR 13 ) m(III)

[0096] In the above formula (III), M and m are the same as in the above formula (I).

[0097] R 12 and R 13 Each independently is a hydrocarbon group or -(R 14 O)r 15 The group shown [here, R 14 is a hydrocarbon group or a silylene group, R 15 is a hydrogen atom, a hydrocarbon group or R 16 3 The group represented by Si- (here, R 16 is a hydrocarbon group, 3 R 16 may be the same or different), r is an integer greater than 1].

[0098] R 12 and R 13 The hydrocarbon group and R 6 and R 7 The hydrocarbon groups are the same.

[0099] R 14 The hydrocarbon group and R 9 In addition, R 15 and R 16 The hydrocarbon group and R 4 and R 5 The hydrocarbon groups are the same.

[0100] r is preferably an integer of 1-10.

[0101] R 12 and R 13 =R 14 O) r -R 15 Specific examples of sulfosuccinic acid derivatives represented by formula (III) when the group represented by R 6 and R 7 =R 9 O) n -R 10 The proton donor represented by the formula (II) is the same as the group represented by the formula (II).

[0102] R 12 and R 13 The hydrocarbon group and R 6 and R 7 The hydrocarbon groups are the same as those of , preferably butyl, hexyl, 2-ethylhexyl, decyl, etc.

[0103] The doping rate of the proton donor to polyaniline is preferably 0.30 to 0.65, more preferably 0.32 to 0.60, further preferably 0.33 to 0.57, and particularly preferably 0.34 to 0.55. If the doping rate is 0.30 or more, the solubility of the polyaniline composite in an organic solvent is sufficiently high.

[0104] The doping rate is defined by (the number of moles of proton donor doped in polyaniline) / (the number of moles of monomer units of polyaniline). For example, a doping rate of 0.5 for a polyaniline composite containing unsubstituted polyaniline and a proton donor means that one proton donor is doped for every two monomer unit molecules of polyaniline.

[0105] If the molar numbers of the proton donor and the monomer unit of polyaniline in the polyaniline composite can be measured, the doping rate can be calculated. For example, when the proton donor is an organic sulfonic acid, the molar number of sulfur atoms from the proton donor and the molar number of nitrogen atoms from the monomer unit of polyaniline are quantified by organic element analysis, and the ratio of these values ​​is obtained, thereby calculating the doping rate.

[0106] The polyaniline composite preferably contains unsubstituted polyaniline and sulfonic acid as a proton donor, and satisfies the following formula (5).

[0107] 0.32≤S 5 / N 5 ≤0.60 (5)

[0108] (Where S 5 is the total number of moles of sulfur atoms contained in the polyaniline composite, N 5 is the total number of moles of nitrogen atoms contained in the polyaniline composite. The above-mentioned number of moles of nitrogen atoms and sulfur atoms are values ​​measured by organic element analysis.

[0109] The component (a) may be used alone or in combination of two or more.

[0110] The content of component (a) is preferably 0.1 to 20 mass %, more preferably 0.5 to 15 mass %, further preferably 1 to 10 mass %, particularly preferably 2 to 5 mass %, based on 100 mass % of the entire composition.

[0111] The method for producing the component (a) is not particularly limited, and the component (a) can be produced, for example, by the method for producing the component (a) described below.

[0112] For example, the proton donor, the aniline corresponding to the polyaniline, and a surfactant (e.g., a nonionic emulsifier) ​​as required are dissolved in a water-immiscible organic solvent (e.g., a hydrocarbon solvent (preferably toluene or xylene)), an acidic aqueous solution (e.g., an aqueous phosphoric acid solution) is added thereto, the reaction liquid having two liquid phases of the water-immiscible organic solvent and water is stirred, and a polymerization initiator (e.g., ammonium persulfate) is added to carry out polymerization.

[0113] After the polymerization, the water-immiscible organic solvent is phase-separated by standing the mixture to obtain a water-immiscible organic solvent solution of the polyaniline composite.

[0114] The solution is transferred to an evaporator, and the volatile components are evaporated to obtain a polyaniline composite (protonated polyaniline).

[0115] (Component (b): phenolic compound)

[0116] The composition of one embodiment of the present invention can improve the conductivity of the obtained conductive film by using a phenol compound.

[0117] The phenol compound is not particularly limited, and is a compound represented by ArOH (wherein Ar is an aryl group or a substituted aryl group). Specifically, examples thereof include substituted phenols such as phenol, o-cresol, m-cresol or p-cresol, o-ethylphenol, m-ethylphenol or p-ethylphenol, o-propylphenol, m-propylphenol or p-propylphenol, o-butylphenol, m-butylphenol or p-butylphenol, o-chlorophenol, m-chlorophenol or p-chlorophenol, o-tert-amylphenol, m-tert-amylphenol or p-tert-amylphenol, salicylic acid, hydroxybenzoic acid, and hydroxynaphthalene; polyphenol compounds such as catechol and resorcinol; and polymer compounds such as phenolic resins, polyphenols, and poly(hydroxystyrene).

[0118] In addition, a phenol compound represented by the following formula (3) can be used.

[0119]

Chemical formula 2

[0120]

[0121] (In formula (3), n1 is an integer of 1 to 5 (preferably 1 to 3).

[0122] R 21 They are alkyl groups having 1 to 10 carbon atoms (preferably 2 to 8, more preferably 3 to 7), alkenyl groups having 2 to 20 carbon atoms, alkylthio groups having 1 to 20 carbon atoms, cycloalkyl groups having 3 to 10 carbon atoms, aryl groups having 6 to 20 carbon atoms, alkylaryl groups having 7 to 20 carbon atoms, or arylalkyl groups having 7 to 20 carbon atoms.

[0123] Next, for the above R 21 Provide explanation.

[0124] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a tert-butyl group, and a tert-amyl group.

[0125] Examples of the alkenyl group include substituents having an unsaturated bond in the molecule of the above-mentioned alkyl group.

[0126] Examples of the cycloalkyl group include cyclopentane and cyclohexane.

[0127] Examples of the alkylthio group include a methylthio group and an ethylthio group.

[0128] Examples of the aryl group include a phenyl group and a naphthyl group.

[0129] Examples of the alkylaryl group and the arylalkyl group include substituents obtained by combining the above-mentioned alkyl groups and aryl groups.

[0130] Among these groups, R 21 , preferably methyl or ethyl.

[0131] In addition, a phenol compound represented by the following formula (3') can be used.

[0132]

Chemical formula 3

[0133]

[0134] (In formula (3'), R 22 It is an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an alkylthio group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkylaryl group having 7 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms.

[0135] R in formula (3') 22 The specific example is the same as R in the above formula (3) 21 same.

[0136] The component (b) may be used alone or in combination of two or more.

[0137] The content of component (b) is preferably 1 to 50 mass %, more preferably 5 to 45 mass %, further preferably 10 to 40 mass %, particularly preferably 20 to 40 mass %, based on 100 mass % of the entire composition.

[0138] From the viewpoint of conductivity, the mass ratio of the content of component (a) to the content of component (b) ("content of component (a)":"content of component (b)") may be 1:1 to 1:20, preferably 1:3 to 1:15, and more preferably 1:5 to 1:10.

[0139] (Ingredient (c): thickener)

[0140] Component (c) is preferably a polyether compound or a cellulose compound.

[0141] Examples of the polyether-based compound include polyethylene oxide (EO)-polypropylene oxide (PO) copolymers (for example, EP1550H (manufactured by Meisei Chemical Industry Co., Ltd.)).

[0142] As cellulose compounds, for example, cellulose ethers (e.g., ethyl cellulose, methyl cellulose), hydroxyethyl cellulose, or hydroxypropyl methyl cellulose can be exemplified. Among them, cellulose ethers can be suitably used from the viewpoint of high thickening effect and easy availability. Among cellulose ethers, ethyl cellulose can be suitably used.

[0143] Examples of the cellulose-based compound include EC-N300 (manufactured by Ashland Co., Ltd.), N200 (manufactured by Ashland Co., Ltd.), and Klucel G (manufactured by Ashland Co., Ltd.).

[0144] The component (c) may be used alone or in combination of two or more.

[0145] The content of the component (c) relative to 100 mass % of the entire composition is, for example, 0.1 mass % or more, 0.2 mass % or more, 0.3 mass % or more, 0.5 mass % or more, 1.5 mass % or more, 2 mass % or more, 0.2 to 10 mass %, 0.3 to 10 mass %, 0.5 to 10 mass %, 1.5 to 5 mass %, or 2 to 3 mass %.

[0146] From the viewpoint of conductivity, the mass ratio of the content of component (a) to the content of component (c) ("content of component (a)":"content of component (c)") is, for example, 1:0.01 to 1:3, 1:0.035 to 1:2, 1:0.1 to 1:1.5, 1:0.1 to 1:1, 1:0.1 to 1:0.9, 1:0.1 to 1:0.7, 1:0.2 to 1:0.7, or 1:0.3 to 1:0.7.

[0147] (Component (d): solvent)

[0148] The composition of one embodiment of the present invention contains a solvent. The solvent is not particularly limited as long as it dissolves component (a), and is preferably an organic solvent. The organic solvent may be a water-soluble organic solvent or an organic solvent that is substantially immiscible with water (a water-immiscible organic solvent).

[0149] The water-soluble organic solvent may be a protic polar solvent or an aprotic polar solvent, and examples thereof include alcohols such as isopropanol, 1-propanol, 1-butanol, 2-butanol, 2-pentanol, benzyl alcohol, alkoxy alcohols (e.g., 1-methoxy-2-propanol, 3-methoxy-1-butanol, 3-methoxy-3-methylbutanol), and ethylene glycol; ketones such as acetone; ethers such as tetrahydrofuran, dioxane, and ethylene glycol mono-tert-butyl ether; and aprotic polar solvents such as N-methylpyrrolidone.

[0150] Examples of water-immiscible organic solvents include hydrocarbon solvents such as hexane, benzene, toluene, xylene, ethylbenzene, tetralin, and IPSOLVENT 1620; halogen-containing solvents such as dichloromethane, chloroform, carbon tetrachloride, dichloroethane, and tetrachloroethane; ester solvents such as ethyl acetate, isobutyl acetate, n-butyl acetate, butyl butyrate, and ethyl lactate; ketone solvents such as methyl isobutyl ketone (MIBK), diisobutyl ketone (DIBK), methyl ethyl ketone, cyclopentanone, and cyclohexanone; and ether solvents such as cyclopentyl methyl ether, 4-methyltetrahydropyran, 1,2-diethoxyethane, and dipropylene glycol dimethyl ether. In addition, as the hydrocarbon solvent, an isoparaffin solvent containing one or more isoparaffins can be used.

[0151] Among them, toluene, xylene, methyl isobutyl ketone, chloroform, trichloroethane and ethyl acetate are preferred because they provide excellent solubility of the component (a).

[0152] The polyaniline composite in component (a) can be dissolved even in alcohols such as isopropyl alcohol, 1-butanol, 2-butanol, 2-pentanol, benzyl alcohol, and alkoxy alcohols. From the viewpoint of reducing environmental load, alcohols are preferred over aromatics such as toluene.

[0153] When an organic solvent is used as the solvent, a mixed organic solvent of a water-immiscible organic solvent and a water-soluble organic solvent at a ratio of 99 to 1:1 to 99 (mass ratio) is preferably used because generation of gel during storage can be prevented and long-term storage can be achieved.

[0154] As the water-immiscible organic solvent of the mixed organic solvent, a low-polarity organic solvent can be used, and the low-polarity organic solvent is preferably a hydrocarbon solvent such as hexane and toluene; a halogen-containing solvent such as chloroform; or an isomeric paraffin solvent.

[0155] As the water-soluble organic solvent of the mixed organic solvent, a highly polar organic solvent can be used, for example, preferably alcohols such as methanol, ethanol, isopropanol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, 3-methoxy-1-butanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone; ethers such as tetrahydrofuran, diethyl ether, ethylene glycol mono-tert-butyl ether.

[0156] The mixed organic solvent may contain one or two or more water-immiscible organic solvents, or may contain one or two or more water-soluble organic solvents.

[0157] The component (d) may be used alone or in combination of two or more.

[0158] The content of the component (d) may be 50 to 99 mass %, 55 to 99 mass %, or 70 to 99 mass % relative to 100 mass % of the entire composition.

[0159] When component (d) contains 3-methoxy-3-methylbutanol, ethylene glycol and IP SOLVENT 1620, it is preferred that component (b) is p-tert-amylphenol and component (c) is EC-N300. In addition, the ratio of "content of component (a)" to "content of component (b)" is preferably 1:3 to 1:10, and particularly preferably 1:5 to 1:8. In addition, the ratio of "content of component (a)" to "content of component (c)" is preferably 1:0.02 to 1:2, and particularly preferably 1:0.1 to 1:0.3.

[0160] When component (d) contains toluene and isopropanol, it is preferred that component (b) is m-cresol and component (c) is EC-N300. In addition, the ratio of "content of component (a)" to "content of component (b)" is preferably 1:3 to 1:10, and particularly preferably 1:7 to 1:9. In addition, the ratio of "content of component (a)" to "content of component (c)" is preferably 1:0.02 to 1:5, and particularly preferably 1:0.1 to 1:2.

[0161] (Component (e): acidic substance and / or salt of acidic substance)

[0162] The composition of one embodiment of the present invention may further contain an acid species different from the above-mentioned proton donor, and may further contain one or more species selected from acidic substances and salts of acidic substances (hereinafter also referred to as "component (e)"). This component is generally used as a heat stabilizer and can further improve the heat resistance of the conductive film.

[0163] The acidic substance may be any of an organic acid which is an acid of an organic compound and an inorganic acid which is an acid of an inorganic compound, and is preferably an organic acid. The acidic substance is preferably an organic acid containing one or more sulfonic acid groups.

[0164] The organic acid having a sulfonic acid group is preferably a cyclic, chain or branched alkylsulfonic acid, a substituted or unsubstituted aromatic sulfonic acid or a polysulfonic acid having one or more sulfonic acid groups.

[0165] Examples of the alkylsulfonic acid include methanesulfonic acid and ethanesulfonic acid. The alkyl group is preferably a linear or branched alkyl group having 1 to 18 carbon atoms.

[0166] Examples of the aromatic sulfonic acid include aromatic sulfonic acids having 6 to 20 carbon atoms, such as sulfonic acids having a benzene ring, sulfonic acids having a naphthalene skeleton, and sulfonic acids having an anthracene skeleton. Examples of the aromatic sulfonic acid include substituted or unsubstituted benzenesulfonic acid, substituted or unsubstituted naphthalenesulfonic acid, and substituted or unsubstituted anthracenesulfonic acid.

[0167] The substituent may be selected from an alkyl group (eg, an alkyl group having 1 to 20 carbon atoms), an alkoxy group (eg, an alkoxy group having 1 to 20 carbon atoms), a hydroxyl group, a nitro group, a carboxyl group, and an acyl group, and may be substituted with one or more substituents.

[0168] Specifically, examples of the aromatic sulfonic acid include compounds represented by the following formula (4) or (5).

[0169]

Chemical formula 4

[0170]

[0171] (In formula (4), l is 1 or more, m is an integer of 0 or more and 5 or less, and n is an integer of 0 or more and 5 or less. When one of m or n is 0, the other is 1 or more.)

[0172]

Chemical formula 5

[0173]

[0174] (In formula (5), q is 1 or more, p is an integer of 0 or more and 7 or less, and R is each independently an alkyl group having 1 to 20 carbon atoms, a carboxyl group, a hydroxyl group, a nitro group, a cyano group, or an amino group.)

[0175] In the formula (4), l is preferably 1 to 3. In the formula (4), m is preferably 1 to 3. In the formula (4), n is preferably 0 to 3.

[0176] In the formula (5), q is preferably 1 to 3. In the formula (5), p is preferably 0 to 3. In the formula (5), R is preferably an alkyl group having 1 to 20 carbon atoms, a carboxyl group, or a hydroxyl group.

[0177] Examples of the aromatic sulfonic acid include 4-sulfophthalic acid, 5-sulfoisophthalic acid, 5-sulfosalicylic acid, 1-naphthalenesulfonic acid, 2-naphthalenesulfonic acid, 2-hydroxy-6-naphthalenesulfonic acid, p-phenolsulfonic acid, toluenesulfonic acid, p-xylene-2-sulfonic acid, 4,4'-biphenyldisulfonic acid, dibenzofuran-2-sulfonic acid, flavianic acid, (+)-10-camphorsulfonic acid, monoisopropylnaphthalenesulfonic acid, 1-pyrenesulfonic acid, etc. Among them, 4-sulfophthalic acid, 5-sulfosalicylic acid, 5-sulfoisophthalic acid, 2-naphthalenesulfonic acid, dibenzofuran-2-sulfonic acid, flavianic acid, 2-hydroxy-6-naphthalenesulfonic acid, and 1-pyrenesulfonic acid are preferred from the viewpoint of improving heat resistance.

[0178] Examples of the salt of the acidic substance include the salts of the compounds listed above, and examples of the counter ion of the salt include sodium, lithium, potassium, cesium, ammonium, calcium, and barium.

[0179] Component (e) may be a hydrate.

[0180] The component (e) may be used alone or in combination of two or more.

[0181] When the component (e) is contained, the content of the component (e) is preferably 0.01 to 10% by mass, more preferably 0.02 to 5% by mass, and even more preferably 0.05 to 3% by mass, based on 100% by mass of the entire composition.

[0182] When component (e) is included, from the viewpoint of heat resistance, the mass ratio of the content of component (a) to the content of component (e) ("content of component (a)":"content of component (e)") can be 1:0.01 to 1:1, preferably 1:0.05 to 1:0.5, and more preferably 1:0.07 to 1:0.1.

[0183] The composition of one embodiment of the present invention may be basically composed of components (a), (b), (c) and (d) and optionally one or more components selected from (e). In this case, inevitable impurities may be contained within a range that does not impair the effects of the present invention.

[0184] For example, 70% by mass or more, 80% by mass or more, 90% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.9% by mass or more, or 100% by mass of the composition of one embodiment of the present invention may be composed of

[0185] Components (a) to (d), or

[0186] Composed of components (a) to (e).

[0187] [Conductive film]

[0188] A conductive film according to one embodiment of the present invention is formed using the above composition.

[0189] For example, a conductive film can be formed by applying the composition of one embodiment of the present invention on a substrate and drying it. A conductive laminate can also be prepared by applying the composition on a substrate such as glass, a resin film, a sheet, or a nonwoven fabric having a desired shape.

[0190] The thickness of the conductive film is usually 1 mm or less, preferably 10 nm to 50 μm.

[0191] From the viewpoint of exerting an effect as a conductive material, the conductivity of the conductive film of one embodiment of the present invention may be, for example, 0.5 S / cm or more, for example, 1 S / cm or more, 4 S / cm or more, 5 S / cm or more, 9 S / cm or more, 10 S / cm or more, 20 S / cm or more, 100 S / cm or more, or 200 S / cm or more, and for example, 400 S / cm or less, or 300 S / cm or less.

[0192] The electrical conductivity of the conductive film was calculated by the following formula using a resistivity meter "Loresta GP" (manufactured by Mitsubishi Chemical Corporation) using a four-terminal method to determine the resistance value.

[0193] Conductivity [S / cm] = distance between electrodes (=1cm) ÷ (resistance [Ω] × film thickness [cm] × film width [cm])

[0194] As a method for applying the composition, a known method such as casting, spraying, dipping, doctor blade, bar coating, spin coating, electrostatic spinning, screen printing, gravure printing, etc. can be used.

[0195] In addition, a step of immersing the conductive film (coating film) in a solution containing the component (e) and drying the solution may be provided. In this case, the component (e) is preferably a compound represented by the formula (4) or a salt thereof.

[0196] The impregnation solution may contain a solvent.

[0197] The solvent is not particularly limited as long as it dissolves component (e), and examples thereof include water, alcohol solvents, ketone solvents, ether solvents, ester solvents, etc. The solvent may be used alone or in combination of two or more.

[0198] Specific examples of the solvent include methanol, ethanol, isopropanol, n-butanol, 1-methoxy-2-propanol, 3-methoxy-1-butanol, 3-methoxy-3-methylbutanol, 1-ethoxy-2-propanol, ethyl acetate, butyl acetate, MIBK, methyl ethyl ketone (MEK), ethylene glycol mono-tert-butyl ether, propylene glycol monomethyl ether acetate, and dipropylene glycol monomethyl ether.

[0199] The content of the component (e) in the immersion solution is preferably 10 to 1200 parts by mass, more preferably 30 to 700 parts by mass, and even more preferably 70 to 400 parts by mass, based on 1 part by mass of the composition obtained by removing the solvent.

[0200] If the amount exceeds 1,200 parts by mass, the acidic substance becomes excessive in the coating film, which may cause deterioration of the polyaniline main chain and reduce the conductivity.

[0201] The content of component (e) in the immersion solution is preferably 0.1% by weight to 10% by weight, more preferably 0.3% by weight to 6% by weight, and even more preferably 0.7% by weight to 3.5% by weight.

[0202] Examples of the impregnation method include immersion and the like.

[0203] The immersion time is preferably 1 minute or longer, more preferably 3 minutes or longer and 200 minutes or shorter. The immersion temperature is preferably 5°C to 50°C.

[0204] Drying after impregnation is preferably performed in an oven, a hot plate, or the like.

[0205] The drying temperature is preferably 80 to 200°C, more preferably 100 to 170°C.

[0206] The drying time is preferably 1 to 180 minutes, more preferably 3 to 60 minutes. If necessary, heating may be performed under reduced pressure. The drying temperature and drying time are not particularly limited and may be appropriately selected according to the material used.

[0207] As described above, the component (e) may be added to the composition or contained in the conductive film obtained from the composition. The component (e) may be added to the composition and the conductive film obtained from the composition may further contain the component (e).

[0208] That is, the conductive film of one embodiment of the present invention sometimes contains a component (e) added before film formation (hereinafter, sometimes referred to as component (e1)) and a component (e) added after film formation (hereinafter, sometimes referred to as component (e2)). Components (e1) and (e2) may be the same or different. In different cases, for example, component (e1) is a compound represented by the above formula (5), and component (e2) is a compound represented by the above formula (4).

[0209] [Capacitor]

[0210] A capacitor according to one embodiment of the present invention includes the above-mentioned conductive film.

[0211] For example, a capacitor can be produced using the composition of one embodiment of the present invention. Specifically, capacitors include electrolytic capacitors and electric double layer capacitors, and electrolytic capacitors include solid electrolytic capacitors.

[0212] When manufacturing a solid electrolytic capacitor, for example, the process includes applying the composition of the present invention to an anode body including an anode and a dielectric of the solid electrolytic capacitor and drying the anode body to form a conductive film on the anode body.

[0213] The capacitor of one embodiment of the present invention has excellent heat resistance and moisture resistance, and therefore is extremely useful, for example, when used for vehicle-mounted applications, circuit substrates in communication base stations, etc. Vehicles such as automobiles are sometimes placed in harsh environments with high temperature and high humidity. In addition, communication base stations sometimes cause the circuit substrate to reach a high temperature due to electronic equipment such as power amplifiers, so capacitors used in these devices are required to have predetermined heat resistance and moisture resistance, and the above-mentioned capacitor can meet this requirement.

[0214] [Battery]

[0215] A battery according to one embodiment of the present invention includes the above-mentioned conductive film.

[0216] The conductive film according to one embodiment of the present invention can be used as a battery material.

[0217] [Conductive laminate, conductive article]

[0218] By applying the composition of one embodiment of the present invention to a substrate such as glass, resin film, sheet, nonwoven fabric, etc. having a desired shape and removing the solvent, a conductive laminate having a conductive film can be manufactured. The conductive laminate is processed into a desired shape by known methods such as vacuum forming and pressure forming to manufacture conductive articles. From the viewpoint of forming, the substrate is preferably a resin film, sheet, or nonwoven fabric.

[0219] As a coating method for the composition to the substrate, known methods such as casting, spraying, dipping, scraper, rod coating, spin coating, electrostatic spinning, screen printing, gravure printing, etc. can be used. When the above-mentioned coating film is dried, the coating film can be heated according to the type of solvent. For example, it is heated at a temperature below 250°C, preferably above 50 and below 200°C under air flow, and then heated under reduced pressure as needed. The heating temperature and heating time are not particularly limited and can be appropriately selected according to the material used.

[0220] In addition, the composition of one embodiment of the present invention can also be used to form a self-supporting molded body without a substrate.

[0221] Example

[0222] Production Example 1 (Production of Polyaniline Composite)

[0223] 32.4 g of "NEOCOL SWC" (sodium di-2-ethylhexyl sulfosuccinate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 13.3 g of aniline, and 0.9 g of "Sorbon T-20" (a nonionic emulsifier having a polyoxyethylene sorbitan fatty acid ester structure, manufactured by Toho Chemical Industry Co., Ltd.) were added to a 1000 mL separable flask and dissolved in 320.4 g of toluene. 450 g of an 8.5 mass % phosphoric acid aqueous solution was added thereto, and the reaction liquid having two liquid phases of toluene and water was stirred, and the internal temperature of the reaction liquid was cooled to -3°C. When the internal temperature of the reaction liquid reached -3°C, a solution obtained by dissolving 39.3 g of APS (ammonium persulfate) in 90.2 g of an 8.5 mass % phosphoric acid aqueous solution was added while stirring the reaction liquid. After the addition, the solution was further stirred for 24 hours while the internal temperature of the solution was kept at -3°C. After stirring was stopped, the contents were transferred to a separatory funnel, and the aqueous phase and the toluene phase were allowed to stand for separation. After separation, the toluene phase was washed once with 180.3 g of 8.5 mass % phosphoric acid aqueous solution and three times with 328.0 g of ion exchange water to obtain a polyaniline composite toluene solution.

[0224] The solution was transferred to an evaporator, heated in a hot water bath at 60° C., and reduced in pressure to distill off volatile components to obtain polyaniline composite 1 (protonated polyaniline). The weight average molecular weight of polyaniline in polyaniline composite 1 was 112,000.

[0225] The weight average molecular weight of polyaniline is measured as follows.

[0226] Dissolve 1.65-1.85 g of lithium bromide in 2000 mL of NMP (N-methyl-2-pyrrolidone) to prepare a 0.01 M (mol / L) lithium bromide NMP solution. Add 14 μL of triethylamine to 10 mL of the 0.01 M (mol / L) lithium bromide NMP solution, stir and dissolve to prepare a uniform solution. Further, drop 50 μL of the polyaniline complex toluene solution obtained in Preparation Example 1, stir and mix, and pass through a 0.45 μm filter to prepare a sample for gel permeation chromatography (GPC) measurement.

[0227] GPC measurement was performed using a sample for GPC measurement and a GPC column (“Shodex KF-806M” manufactured by Showa Denko K.K., two connected) under the following measurement conditions.

[0228] Solvent: NMP containing 0.01M (mol / L) LiBr

[0229] Flow rate: 0.70mL / min

[0230] Column temperature: 60°C

[0231] Injection volume: 100 μL

[0232] UV detection wavelength: 270nm

[0233] The weight average molecular weight obtained by the above method is a polystyrene (PS) conversion value.

[0234] The doping ratio of the proton donor (sodium di-2-ethylhexylsulfosuccinate) to polyaniline was 0.36.

[0235] Example 1 (Preparation of composition)

[0236] 30 g of 3-methoxy-3-methylbutanol (MMB), 10 g of ethylene glycol (EG), 20 g of IP SOLVENT 1620 (IP1620, manufactured by Idemitsu Kosan Co., Ltd.), and 40 g of p-tert-amylphenol (tAP) (component (b)) were stirred and mixed until uniform to prepare a mixed solvent A. 5 g of polyaniline composite 1 and 0.1 g of EC-N300 (N300, ethyl cellulose, a compound having the following structure, manufactured by Ashland Co., Ltd.) were dissolved in 94.9 g of the mixed solvent A to obtain a polyaniline composite solution 1.

[0237] 1 g of 2-naphthalenesulfonic acid (NSA) hydrate (since the amount of hydrate is very small, NSA is assumed to be 1 g) was dissolved in 9 g of 3-methoxy-3-methylbutanol (MMB) to obtain a uniform 2-naphthalenesulfonic acid solution 1.

[0238] 0.188 g of 2-naphthalenesulfonic acid solution 1 was added to 5 g of polyaniline composite solution 1, and the mixture was stirred in a 30°C water bath for 30 minutes to obtain a composition.

[0239] In Table 1, the component (d) is shown as the total amount of each component (d) (the same applies hereinafter).

[0240]

Chemical formula 6

[0241]

[0242] (Determination of viscosity)

[0243] The viscosity of the obtained composition was measured in the range of liquid temperature of 23 to 24° C. using a tuning fork vibration viscometer SV-1H (manufactured by A&D Corporation).

[0244] The results are shown in Table 1.

[0245] (Manufacturing of conductive film)

[0246] 1 mL of the above composition was applied to Figure 1 The upper surface of the glass substrate 1 shown has an indium tin oxide (ITO) electrode 2 formed on the surface by patterning. The coating is performed by spin coating in an air atmosphere. The rotation time of the glass substrate 1 after the composition is dripped is set to 15 seconds, and the rotation speed of the glass substrate 1 is set to 2000-2500 rpm. Thereafter, the glass substrate 1 is dried to form a conductive film. Drying is performed at 80°C for 5 minutes.

[0247] (Evaluation of conductive film (electrical conductivity))

[0248] like Figure 2 As shown, the portion of the obtained conductive film 5 covering the terminal of the ITO electrode is scraped off in the air atmosphere to expose the terminal of the ITO electrode 2 on the surface. The resistance value is measured using a resistivity meter "Loresta GP" (Mitsubishi Chemical Corporation) based on the four-terminal method using the ITO electrode 2 exposed on the surface.

[0249] The film thickness and film width of the conductive film were measured using a scanning white interference microscope VS1330 (manufactured by Hitachi High-Tech Co., Ltd.) The conductivity of the conductive film was calculated from the measured values ​​using the following formula.

[0250] Conductivity [S / cm] = distance between electrodes (=1cm) ÷ (resistance [Ω] × film thickness [cm] × film width [cm])

[0251] The results are shown in Table 1.

[0252] Example 2

[0253] 5 g of the polyaniline composite 1 and 0.5 g of N300 were dissolved in 94.5 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 2.

[0254] 0.188 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 2, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0255] The obtained composition was evaluated in the same manner as in Example 1. Table 1 shows the results.

[0256] Example 3

[0257] 37.5 g of MMB, 12.5 g of EG, 25 g of tAP, and 25 g of IP1620 were stirred and mixed until uniform to prepare a mixed solvent B. 5 g of the polyaniline composite 1 and 0.5 g of N300 were dissolved in 94.5 g of the mixed solvent B to obtain a polyaniline composite solution 3.

[0258] 0.188 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 3, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0259] The obtained composition was evaluated in the same manner as in Example 1. Table 1 shows the results.

[0260] Comparative Example 1

[0261] 50 g of MMB, 17 g of EG, and 33 g of IP1620 were stirred and mixed to prepare a mixed solvent C. The mixed solvent C was not uniformly dissolved. 5 g of polyaniline complex 1 and 0.5 g of N300 were added to 94.5 g of the mixed solvent C to obtain a polyaniline complex solution 4. In the polyaniline complex solution 4, the polyaniline complex 1 was not dissolved, and a non-uniform solution was obtained.

[0262] 0.188 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 4, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0263] Since the polyaniline composite 1 was not dissolved in the composition, the composition was non-uniform, and therefore accurate viscosity measurement could not be performed. In Table 1, this is indicated as "-" (the same applies hereinafter).

[0264] In addition, a coating film was prepared by spin coating in the same manner as in Example 1, but a uniform coating film could not be prepared, and the resistance value was above the upper limit of measurement, and a coating film having conductivity could not be prepared. In Table 1, this is indicated as "-" (the same below).

[0265] Comparative Example 2

[0266] 5 g of the polyaniline composite 1 was dissolved in 95 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 5 .

[0267] 0.188 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 5, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0268] The obtained composition was evaluated in the same manner as in Example 1. Table 1 shows the results.

[0269] Comparative Example 3

[0270] 5 g of the polyaniline composite 1 was added to 95 g of the mixed solvent C prepared in Comparative Example 1 to obtain a polyaniline composite solution 6. The polyaniline composite 1 was not dissolved in the mixed solvent C, and a non-uniform solution was obtained.

[0271] 0.188 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 6, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0272] Since the polyaniline composite 1 was not dissolved in the composition, the composition was a non-uniform composition, and therefore accurate viscosity measurement could not be performed.

[0273] In addition, a coating film was prepared by spin coating in the same manner as in Example 1, but a uniform coating film could not be prepared, and the resistance value was more than the upper limit of measurement, and a coating film having conductivity could not be prepared.

[0274] Comparative Example 4

[0275] 5 g of the polyaniline complex 1 was dissolved in 95 g of the mixed solvent B prepared in Example 3 to obtain a polyaniline complex solution 7 .

[0276] 0.188 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 7, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0277] The obtained composition was evaluated in the same manner as in Example 1. Table 1 shows the results.

[0278] Examples 11 to 13, Examples 21 to 22, Examples 31 to 32, Comparative Example 11, Comparative Example 21, and Comparative Example 31

[0279] Examples 11, 21, and 31 were produced and evaluated in the same manner as in Example 1, except that the components (c) shown in Tables 2 to 4 were used. The results are shown in Tables 2 to 4.

[0280] Examples 12, 22, and 32 were produced and evaluated in the same manner as in Example 2 except that the components (c) shown in Tables 2 to 4 were used. The results are shown in Tables 2 to 4.

[0281] Comparative Examples 11, 21, and 31 were produced and evaluated in the same manner as in Comparative Example 1, except that the components (c) shown in Tables 2 to 4 were used. The results are shown in Tables 2 to 4.

[0282] Example 13

[0283] 5 g of the polyaniline composite 1 and 1.0 g of N200 were dissolved in 94 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 8 .

[0284] 0.188 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 8, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0285] The obtained composition was evaluated in the same manner as in Example 1. Table 2 shows the results.

[0286] (Evaluation of viscosity ratio 1)

[0287] In Examples 1 to 3, Examples 11 to 13, Examples 21 to 22, Examples 31 to 32, Comparative Examples 1 to 4, Comparative Example 11, Comparative Example 21 and Comparative Example 31, the values ​​obtained by dividing the respective viscosity values ​​by the viscosity value of Comparative Example 2 are shown in Tables 1 to 4. "-" indicates that evaluation was not possible.

[0288] Components (c) other than the components used in Example 1 are shown below.

[0289] N200: Ethyl cellulose, a compound of the following structure, manufactured by Ashland

[0290]

Chemical formula 7

[0291]

[0292] G: Klucel G, hydroxypropyl cellulose, a compound of the following structure, manufactured by Ashland

[0293]

Chemical formula 8

[0294]

[0295] EP1550H: Ethylene oxide / propylene oxide copolymer, manufactured by Meisei Chemical Industry Co., Ltd.

[0296]

Table 1

[0297]

[0298]

Table 2

[0299]

[0300]

Table 3

[0301]

[0302]

Table 4

[0303]

[0304] Embodiment 41

[0305] 7 g of the polyaniline composite 1 and 1 g of N300 were dissolved in 92 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 9.

[0306] 0.263 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 9, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0307] The obtained composition was evaluated in the same manner as in Example 1. Table 5 shows the results.

[0308] Embodiment 42

[0309] 7 g of the polyaniline composite 1 and 2 g of N300 were dissolved in 91 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 10 .

[0310] 0.263 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 10, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0311] The obtained composition was evaluated in the same manner as in Example 1. Table 5 shows the results.

[0312] Comparative Example 41

[0313] 7 g of the polyaniline composite 1 was dissolved in 93 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 11 .

[0314] 0.263 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 11, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0315] The obtained composition was evaluated in the same manner as in Example 1. Table 5 shows the results.

[0316] (Evaluation of viscosity ratio 2)

[0317] Table 5 shows the values ​​obtained by dividing the viscosity values ​​of Examples 41 to 42 and Comparative Example 41 by the viscosity value of Comparative Example 41.

[0318]

Table 5

[0319]

[0320] Embodiment 51

[0321] 10 g of the polyaniline composite 1 and 1 g of N300 were dissolved in 89 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 12 .

[0322] 0.376 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 12, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0323] The obtained composition was evaluated in the same manner as in Example 1. Table 6 shows the results.

[0324] Comparative Example 51

[0325] 10 g of the polyaniline composite 1 was dissolved in 90 g of the mixed solvent A prepared in Example 1 to obtain a polyaniline composite solution 13 .

[0326] 0.376 g of the 2-naphthalenesulfonic acid solution 1 prepared in Example 1 was added to 5 g of the polyaniline composite solution 13, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition.

[0327] The obtained composition was evaluated in the same manner as in Example 1. Table 6 shows the results.

[0328] (Evaluation of viscosity ratio 3)

[0329] Table 6 shows the values ​​obtained by dividing the viscosity values ​​of Example 51 and Comparative Example 51 by the viscosity value of Comparative Example 51.

[0330]

Table 6

[0331]

[0332] Example 61 (Preparation of composition)

[0333] 95 g of toluene (Tol) and 5 g of isopropyl alcohol (IPA) were stirred and mixed until uniform to prepare a mixed solvent D. 0.30 g of polyaniline composite 1 and 0.03 g of EC-N300 (N300, ethyl cellulose, a compound of the following structure, manufactured by Ashland) were dissolved in 7.25 g of the mixed solvent D to obtain a polyaniline composite solution 14.

[0334] 2.42 g of m-cresol was added to the polyaniline composite solution 14, and the mixture was stirred in a water bath at 30°C for 30 minutes to obtain a composition weighing 10 g in total.

[0335] The viscosity of the obtained composition was measured in the same manner as in Example 1. The electrical conductivity of the obtained conductive film was determined in the same manner as in Example 1. The results are shown in Table 7.

[0336] Examples 62 to 69 and Comparative Examples 61 to 65

[0337] The production and evaluation were carried out in the same manner as in Example 61 except that the blending amounts were set as shown in Tables 7 and 8. The results are shown in Tables 7 and 8.

[0338] (Evaluation of viscosity ratio 4)

[0339] Tables 7 and 8 show the values ​​obtained by dividing the viscosity values ​​of Examples 61 to 69 and Comparative Examples 61 to 65 by the viscosity value of Comparative Example 65.

[0340] exist Figure 3 ] A graph showing the synergistic effect of component (b) and component (c) using Examples 61 to 65 and Comparative Examples 61 to 64 is shown. Examples 61 to 65 contain 24.2% by mass of component (b). On the other hand, Comparative Examples 61 to 64 do not contain component (b).

[0341] The vertical axis represents viscosity, and the horizontal axis represents the blending amount of the component (c).

[0342] Even when the amount of component (c) added is small, the viscosity is increased by the synergistic effect of components (b) and (c). Figure 3 The two ends of the mixture are indicated by solid arrows), but as the amount of component (c) increases, the viscosity increases significantly due to the synergistic effect of components (b) and (c) ( Figure 3 The two ends are indicated by dashed arrows).

[0343]

Table 7

[0344]

[0345]

Table 8

[0346]

[0347] Industrial Applicability

[0348] The composition of the present invention and the conductive film of the present invention can be used for capacitors, batteries, and the like.

[0349] Several embodiments and / or examples of the present invention have been described in detail above, but those skilled in the art can easily make various changes to these illustrative embodiments and / or examples without departing from the novel teachings and effects of the present invention. Therefore, these various changes are included in the scope of the present invention.

[0350] The contents of the documents described in this specification and the applications on which the Paris Convention priority claim of the present application is based are all incorporated into this specification by reference.

Claims

1. A composition comprising: Component (a): conductive polymer; Component (b): phenolic compounds; Component (c): a tackifier; and Component (d): solvent.

2. The composition according to claim 1, wherein The component (a) is a polyaniline composite in which a proton donor is doped into substituted or unsubstituted polyaniline.

3. The composition according to claim 2, wherein The proton donor is a proton donor represented by the following formula (I), M(XARn)m(I) In formula (I), M is a hydrogen atom, an organic free radical or an inorganic free radical, X is an acidic group, A is a hydrocarbon group optionally containing a substituent, R is each independently -R 1 、-OR 1 、-COR 1 、-COOR 1 、-CO(COR 1 ) or -CO (COOR 1 ) shown as a substituent, R 1 is a hydrocarbon group having 4 or more carbon atoms which may contain a substituent, a silyl group, an alkylsilyl group, -(R 2 O) x -R 3 The group shown, or -(OSiR 3 2) x -OR 3 The group shown, wherein R 2 is an alkylene group, R 3 are respectively the same or different hydrocarbon groups, x is an integer greater than 1, n is an integer greater than or equal to 2, m is the valence of M.

4. The composition according to any one of claims 1 to 3, wherein The content of the component (c) is 0.1% by mass or more relative to 100% by mass of the entire composition.

5. The composition according to any one of claims 1 to 4, wherein The mass ratio of the content of the component (a) to the content of the component (c) is 1:0.01 to 1:

2.

6. The composition according to any one of claims 1 to 5, wherein The component (c) is a polyether compound or a cellulose compound. 7 . The composition according to claim 1 , which has a viscosity of 2 to 1000 mPa·s. 8 . A conductive film formed using the composition according to claim 1 . 9 . A capacitor comprising the conductive film according to claim 8 . 10 . A battery comprising the conductive film according to claim 8 .